Thermodynamic spectral and kinetic analysis of the removal of Cu(II) from aqueous solution by sodium carbonate treated rice husk. Issue 8 (3rd July 2019) - Acharya, Jyotikusum; Kumar, Upendra; Meikap, B. C.
Abstract: A new adsorbent for removing copper ions from aqueous solutions has been developed and characterized. The present study deals with the sorption of Cu(II) from aqueous solution on chemically pretreated sodium carbonate-treated rice husk (SCRH). The physico-chemical characteristics of rice husks were investigated to analyze their suitability to adsorb Cu(II) ions from water and wastewater. The raw rice husk (RRH), SCRH and Cu(II) adsorbed rice husk were analyzed by SEM-EDAX analysis. FTIR spectroscopy was also applied to identify functional groups, capable of adsorbing metal ions. Batch kinetic studies were conducted for the adsorption of Cu(II) on SCRH. It has been observed that 92.9–96.0% removal of Cu(II) is achieved at 4.8 mg of Cu(II)/g of adsorbent, adsorbent dose of 10 g L –1 and initial Cu(II) concentration of 10 mg L –1 in a temperature range of 15–50 °C. It was observed that the adsorption of Cu(II) on SCRH followed pseudo second-order kinetic and time to achieve equilibrium was found to be 60 min. The maximum uptake (97%) of Cu (II) was observed at pH 6. In this paper, an attempt has also been made to develop simple and readily understandable thermodynamic parameters related to sorption process at the equilibrium for understanding the adsorption mechanism. The Gibbs free energy Δ G ° values for the adsorption processes of Cu(II) at 15, 30, 40 and 50 °C were calculated as –6.16, –6.84, –8.01 and –8.53 kJ mol –1, respectively. The negative value of Δ G ° indicates spontaneity of adsorption. The values of Δ H ° and Δ S ° for Cu(II) adsorption were calculated as 14.37 kJ mol –1 and 70.92 J K –1 mol –1, respectively. The activation energy for the adsorption of Cu(II) was found to be 9 kJ mol –1 which is a characteristic for diffusion limited processes.